Sensing alterations of the local environment of 3d, 4d, and 4f central ions in polyoxopalladates with soft X-ray magnetic dichroisms - Schmitz-Antoniak, Carolin; Izarova, Natalya; Stuckart, Maria; Smekhova, Alevtina; Schmitz, Detlef; Shams, S. Fatemeh; Siemensmeyer, Konrad; Giesen, Margret; Koegerler, Paul (Journal of Magnetism and Magnetic Materials, 2020)
Polyoxopalladates hosting 3d, 4d or 4f central ions form a new class of molecular materials with well-defined, tunable morphology and ions coordination to be considered as model systems for basic research. We investigated the isotropic X-ray absorption near-edge structure (XANES), X-ray magnetic circular dichroism (XMCD), and X-ray magnetic linear dichroism (XMLD) to monitor the influence of symmetry changes on electronic and magnetic properties. After a brief introductory review about recent results on 3d and 4d transition metal ions, we (i) show that a change of the coordination symmetry from cubic eightfold (tetrahedral) to sixfold (octahedral) reduces the magnetic moment of Co2+ significantly and (ii) investigate whether axial distortions can modify the 4f states of trivalent lanthanide ions. While for Gd3+ there is no effect visible within experimental uncertainties, changes were observed for Dy3+ and Ho3+. The results are compared to atomic multiples calculations including the intraatomic spin-dipole term < T-z >. Furthermore, several experimental pitfalls are discussed that may lead to misinterpretation of X-ray absorption data but can be excluded in the present study.
CRIS-Team WoS Importer:2020-10-16